GE_GERICHTE P/4002/2019 vom 12. März 2019 - GE Cour de justice (2019)
CLASSEMENT DE LA PROCÉDURE;CONTRAINTE(DROIT PÉNAL);TENTATIVE(DROIT PÉNAL);DROIT D'ÊTRE ENTENDU;DROIT DE RÉPONSE | CPP.310; Cst.29.al2; CP.181; CP.22.al1